RefSeq database growth influences the accuracy of k-mer-based lowest common ancestor species identification - Daniel J. Nasko; Sergey Koren; Adam M. Phillippy; Todd J. Treangen (Genome Biology, 2018)
Abstract In order to determine the role of the database in taxonomic sequence classification, we examine the influence of the database over time on k-mer-based lowest common ancestor taxonomic classification. We present three major findings: the number of new species added to the NCBI RefSeq database greatly outpaces the number of new genera; as a result, more reads are classified with newer database versions, but fewer are classified at the species level; and Bayesian-based re-estimation mitigates this effect but struggles with novel genomes. These results suggest a need for new classification approaches specially adapted for large databases.